2015
DOI: 10.1007/s00586-015-3759-7
|View full text |Cite
|
Sign up to set email alerts
|

Patients with spinal deformity over the age of 75: a retrospective analysis of operative versus non-operative management

Abstract: In the largest series to date comparing operative and non-operative management of adult spinal deformity in elderly patients greater than 75 years of age, reconstructive surgery provides significant improvements in pain and disability over a 2-year period. Furthermore, operative patients were more likely to reach MCID than non-operative patients. When counseling elderly patients with ASD, such data may be helpful in the decision-making process regarding treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…The presence of lateral listhesis, spondylolisthesis, and sagittal or coronal decompensation, despite a low Cobb angle, is believed to be more important in decision-making Lonergan et al (33) R -Age alone should not be the deciding factor or a contraindication for patients in their 8 th decade of life who are incapacitated by their painful spinal deformity Cho et al (10) Review -Short fusion is indicated in cases with less Cobb angle, minimal rotational deformity, and no coronal and sagittal imbalance. Long fusion is indicated in cases of severe Cobb angle and coronal and sagittal imbalance Sciubba et al (50) PR >20°Surgery provides significant improvements in pain and disability in patients aged >75 Scheer et al (44) PR >20°Surgical management resulted in significantly greater improvement in both back and leg pain severity than nonsurgical management. Moreover, patients whose ASD was managed nonsurgically were more likely to experience no improvement or worsening of their pain Smith et al (58) P >20°Operative treatment for ASD can provide significant improvement of HRQoL at a minimum 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of lateral listhesis, spondylolisthesis, and sagittal or coronal decompensation, despite a low Cobb angle, is believed to be more important in decision-making Lonergan et al (33) R -Age alone should not be the deciding factor or a contraindication for patients in their 8 th decade of life who are incapacitated by their painful spinal deformity Cho et al (10) Review -Short fusion is indicated in cases with less Cobb angle, minimal rotational deformity, and no coronal and sagittal imbalance. Long fusion is indicated in cases of severe Cobb angle and coronal and sagittal imbalance Sciubba et al (50) PR >20°Surgery provides significant improvements in pain and disability in patients aged >75 Scheer et al (44) PR >20°Surgical management resulted in significantly greater improvement in both back and leg pain severity than nonsurgical management. Moreover, patients whose ASD was managed nonsurgically were more likely to experience no improvement or worsening of their pain Smith et al (58) P >20°Operative treatment for ASD can provide significant improvement of HRQoL at a minimum 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, there is literature evidence of supporting conservative interventions for selected cases. Non-operative methods should be tried first and all means be consumed before the talk of surgery (32,50,56 ) . Conservative treatment includes aerobic exercise, aquatics/pool therapy, strength training, stretching exercises, postural training, body mechanics physical agents methods, analgesics, nonsteroidal anti-inflammatory drugs, narcotics, pain management, epidural blocks, facet or nerve root injections, bracing, bed rest, weight loss programs or "no treatment".…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…Furthermore, surgically treated patients were more likely to reach MCID than non-operative patients”. 10 …”
Section: What Is the ‘Ideal’ Treatment For Asd: Surgical Or Non-surgimentioning
confidence: 99%
“…Over the past 10 years, there has been an increased focus on the evaluation and treatment of adult scoliosis [1][2][3]. Several studies have examined the complexity of adult scoliosis patients, based in part on the interaction of the deformity with the normal aging processes of the spine [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the complexity of adult scoliosis patients, based in part on the interaction of the deformity with the normal aging processes of the spine [2][3][4][5][6][7]. The intersection between degeneration and deformity is most evident in relation to the lumbar spine.…”
Section: Introductionmentioning
confidence: 99%